Quantifying the influence of climate and biological drivers on the interannual variability of carbon exchanges in European forests through process-based modelling - DELPIERRE, N.; SOUDANI, K.; François, C.; Le Maire, G.; BERNHOFER, C.; Kutsch, W.; Misson, L.; Rambal, S.; Vesala, T.; Dufrêne, E. (Agricultural and Forest Meteorology, 2012)
It is necessary to increase our understanding of the inﬂuence of climate and biological drivers on the interannual variations in carbon (C) exchange between forests and the atmosphere. To this aim, a processbasedmodel(CASTANEA) was used for simulating C exchanges over four European forests, encompassing a broad latitudinal gradient (from Mediterranean to boreal climate zones), for the years 2000–2007. CASTANEA reproduced 74–95% of the daily and 35–84% of the annual variance in daytime net ecosystem productivity (NEP). Constrained simulations allowed us to isolate the individual contributions of climatic drivers (radiation, temperature and relative humidity), hydrological drivers (soil water) and biological drivers (canopy dynamics, the thermal acclimation of photosynthetic capacities in evergreens, and vegetative and microbial C pools) to the anomalies in C exchange for timescales ranging from daily to annual. Orthonormal wavelet transformation of these single-contribution time series allowed us to quantify the individual drivers’ inﬂuences on ﬂux variance across time scales. High frequency departures from mean annual C exchange patterns were mostly caused by hydroclimate modulations (87–99% of the ﬂux variance from daily to weekly scales). The integration of these anomalies at the annual scale yielded a higher contribution of biological drivers: we identiﬁed a primary controller of gross primary production (GPP) variations through modulations of soil water in both the Mediterranean Quercus ilex and the temperate Fagus sylvatica forests; we also identiﬁed at the annual scale a complex determinism for both coniferous sites, with an unexpectedly higher contribution of the thermal acclimation driver at the temperate (warmer) site. Although all but one site experienced structural perturbations during the study period, interannual variations in ecosystem respiration (Reco) were readily related to changes in temperature and soil water, with a low contribution from variations in C pools at the annual scale. As a result of the preponderant dependence of net ecosystem production (NEP) on GPP ﬂuxes, the inferred determinism of simulated net exchanges appeared similar to that of GPP. However, compensations occurred, leading, for example, to a much lower inﬂuence of soil water modulations on NEP than on GPP or Reco at the Mediterranean site.
Keywords: Carbon exchanges; Climate drivers; Ecosystem functional properties; European forests; Interannual variability; process-based model

Litter decomposition in Mediterranean ecosystems: Modelling the controlling role of climatic conditions and litter quality - Incerti, Guido; Bonanomi, Giuliano; Giannino, Francesco; Rutigliano, Flora Angela; Piermatteo, Daniela; Castaldi, Simona; De Marco, Anna; Fierro, Angelo; Fioretto, Antonietta; Maggi, Oriana; Papa, Stefania; Persiani, Anna Maria; et al. (Applied Soil Ecology, 2011)
A new process-based model of litter decomposition, characterized by detailed climatic data input and simple litter quality parameters, is proposed. Compared to existing litter carbon models, speciﬁc implementations for temperature and moisture limiting effects have been adopted. The model is capable to represent decomposition processes in Mediterranean ecosystems, with summer drought slowing down, even at optimal temperatures, the litter decay rates of sclerophyll plants whose leaf masses are rich in structural compounds and low in N content. The model was calibrated by a best ﬁtting procedure of two different datasets. First, unpublished results of litterbag experiments on leaf litter of 9 Mediterranean species, decomposing under controlled and not limiting temperature and water conditions, have been used to estimate the decay rate dependency from litter quality that was deﬁned by only three initial C pools (labile, stable and recalcitrant compounds) instead of traditional N-based indices. Second, a set of published data from three medium-term ﬁeld experiments on a single species, Phillyrea angustifolia, decomposing under different climatic conditions, have been used to estimate the limiting effects of temperature and moisture. The model was then validated against published data on seven other species and showed a correct reproduction ofthemajor patterns of littermass loss during decomposition processes of other seven different Mediterranean species. The model simulations, satisfactory for different litter types under a wide range of climatic conditions, suggest that factors which were not taken into account, such as initial litter N contents, microclimatic variations related to stand structure, soil chemistry and texture, and microbial communities, are not very signiﬁcant for assessing decomposition dynamics in Mediterranean ecosystems. The minimal requirements of input data, the simple structure, and the easiness of parameterisation make our model, among the many other available litter carbon models, an attractive alternative for different research purposes, at least for Mediterranean ecosystems.
Keywords: C model; C/N ratio; Initial C pools; process-based model; Semi-arid ecosystems; System dynamics

Exceptional carbon uptake in European forests during the warm spring of 2007: a data–model analysis - DELPIERRE, N.; SOUDANI, K.; François, C.; Köstner, B.; Pontailler, J.-Y.; NIKINMAA, E.; Misson, L.; Aubinet, M.; BERNHOFER, C.; Granier, A.; GRÜNWALD, T.; HEINESCH, B.; et al. (Global Change Biology, 2009)
Temperate and boreal forests undergo drastic functional changes in the springtime, shifting within a few weeks from net carbon (C) sources to net C sinks. Most of these changes are mediated by temperature. The autumn 2006–winter 2007 record warm period was followed by an exceptionally warm spring in Europe, making spring 2007 a good candidate for advances in the onset of the photosynthetically active period. An analysis of a decade of eddy covariance data from six European forests stands, which encompass a wide range of functional types (broadleaf evergreen, broadleaf deciduous, needleleaf evergreen) and a wide latitudinal band (from 44° to 62°N), revealed exceptional fluxes during spring 2007. Gross primary productivity (GPP) of spring 2007 was the maximum recorded in the decade examined for all sites but a Mediterranean evergreen forest (with a +40 to +130 gC m−2 anomaly compared with the decadal mean over the January–May period). Total ecosystem respiration (TER) was also promoted during spring 2007, though less anomalous than GPP (with a +17 to +93 gC m−2 anomaly over 5 months), leading to higher net uptake than the long-term mean at all sites (+12 to +79 gC m−2 anomaly over 5 months). A correlative analysis relating springtime C fluxes to simple phenological indices suggested spring C uptake and temperatures to be related. The CASTANEA process-based model was used to disentangle the seasonality of climatic drivers (incoming radiation, air and soil temperatures) and biological drivers (canopy dynamics, thermal acclimation of photosynthesis to low temperatures) on spring C fluxes along the latitudinal gradient. A sensitivity analysis of model simulations evidenced the roles of (i) an exceptional early budburst combined with elevated air temperature in deciduous sites, and (ii) an early relief of winter thermal acclimation in coniferous sites for the promotion of 2007 spring assimilation.
Keywords: 13 october 2008; august 2008 and accepted; European forests; functional drivers; net carbon uptake; process-based model; received 30 may 2008; revised version received 30; spring

Exceptional carbon uptake in European forests during the warm spring of 2007: a data–model analysis - DELPIERRE, N.; SOUDANI, K.; François, C.; Köstner, B.; Pontailler, J.-Y.; NIKINMAA, E.; Misson, L.; Aubinet, M.; BERNHOFER, C.; GRANIER, a; GRÜNWALD, T.; HEINESCH, B.; et al. (Global Change Biology, 2009)
Temperate and boreal forests undergo drastic functional changes in the springtime, shifting within a few weeks from net carbon (C) sources to net C sinks. Most of these changes are mediated by temperature. The autumn 2006–winter 2007 record warm period was followed by an exceptionally warm spring in Europe, making spring 2007 a good candidate for advances in the onset of the photosynthetically active period. An analysis of a decade of eddy covariance data from six European forests stands, which encompass a wide range of functional types (broadleaf evergreen, broadleaf deciduous, needleleaf evergreen) and a wide latitudinal band (from 44° to 62°N), revealed exceptional fluxes during spring 2007. Gross primary productivity (GPP) of spring 2007 was the maximum recorded in the decade examined for all sites but a Mediterranean evergreen forest (with a +40 to +130 gC m−2 anomaly compared with the decadal mean over the January–May period). Total ecosystem respiration (TER) was also promoted during spring 2007, though less anomalous than GPP (with a +17 to +93 gC m−2 anomaly over 5 months), leading to higher net uptake than the long-term mean at all sites (+12 to +79 gC m−2 anomaly over 5 months). A correlative analysis relating springtime C fluxes to simple phenological indices suggested spring C uptake and temperatures to be related. The CASTANEA process-based model was used to disentangle the seasonality of climatic drivers (incoming radiation, air and soil temperatures) and biological drivers (canopy dynamics, thermal acclimation of photosynthesis to low temperatures) on spring C fluxes along the latitudinal gradient. A sensitivity analysis of model simulations evidenced the roles of (i) an exceptional early budburst combined with elevated air temperature in deciduous sites, and (ii) an early relief of winter thermal acclimation in coniferous sites for the promotion of 2007 spring assimilation.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 13 october 2008; august 2008 and accepted; European forests; functional drivers; net carbon uptake; process-based model; received 30 may 2008; revised version received 30; spring